The efficacy and safety of tenofovir in the prevention of Hepatitis B virus recurrence following liver transplantation - Derviş Hakim, Gözde; Akarsu, Mesut; Karademir, Sedat; Unek, Tarkan; Astarcıoğlu, İbrahim (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: In this study, a tenofovir disoproxil fumarate (TDF) + hepatitis B immunoglobulin (HBIG) regimen was compared with lamivudine (LAM) + HBIG to determine the efficacy and safety of TDF in the prevention of hepatitis B virus (HBV) recurrence following liver transplantation (LT). Materials and Methods: Thirty-six patients, 18 treated with TDF+HBIG (TDF group) and 18 with LAM+HBIG (LAM group), were evaluated retrospectively over a median 36-month follow-up in the Liver Transplantation Outpatient Unit of Dokuz Eylül University after having an LT. In the TDF group, TDF treatment was initiated in six patients due to resistance to LAM, in one patient due to relapse, in three patients to prevent relapse, and in eight patients due to de novo hepatitis. In the LAM group, LAM therapy was initiated in two patients due to de novo hepatitis and in 16 patients to prevent relapse. Results: In the TDF group, an increase of greater than 0.5 mg/dL in creatinine values was observed in two patients. In the LAM group, creatinine values did not increase to greater than 0.5 mg/dL. No cases of acute renal failure associated with TDF or LAM, mild or serious adverse events, or HBV recurrence were observed among the patients. Glomerular filtration rates (GFRs) of these patients were calculated with a modification of renal disease (MDRD) formulation. There was no significant difference (p<0.05) in the GFRs between the two groups. Conclusion: The results of this study, after a 36-month follow-up period, were encouraging and demonstrated that TDF therapy is safe and efficacious in treating HBV-positive organ transplant patients. However, patients should be monitored carefully in terms of renal function. Given the limited experience with TDR in LT, this study is of importance due to its long follow-up period.